La participación de los adolescentes en el fútbol profesional ecuatoriano y su impacto en el derecho laboral - Barrigas Izurieta, Alexander Fabricio (2024)
The purpose of this research is to legally analyze the participation of adolescents in Ecuadorian professional soccer to identify their labor rights. It is necessary to mention for this purpose that adolescents whose age range between 15 and 18 years who belong to a professional soccer club are subject to the rules that are managed internally, just like soccer players who exceed the aforementioned age, this same considered a group of priority attention as determined by the Supreme Standard of our country, obliges football clubs to comply with certain rights that are established in the applicable legal bodies. The research carried out aims to determine whether the policies and regulations that regulate this sporting activity guarantee and ensure the labor rights of adolescents in Ecuadorian professional soccer. This will undoubtedly help to identify the different strengths and weaknesses to which adolescent soccer players who are part of a soccer club and, at the same time, participate in official competitions, may be exposed. Due to the characteristics of this research, we´re based on a qualitative approach using deductive legal, legal-analytical, dogmatic, and descriptive methods. In addition, surveys conducted with soccer players and lawyers specializing in contracting and labor law and interviews conducted with judges with experience in labor matters were analyzed. The results achieved because of the research and analysis of surveys and interviews reflect that there is a precariousness of legal regulations applicable to this group of priority attention focused on sports because the regulatory bodies present several legal loopholes that allow violation of rights that correspond to adolescents.